A Rare and Serious Unforeseen Complication of Cutting Balloon Angioplasty - Praveen Vemula; Jagadeesh K. Kalavakunta; George S. Abela; Milind Karve (Case Reports in Cardiology)
Cutting balloon angioplasty (CBA) is one of the adept ways of treating “in-stent restenosis.” Various complications related to cutting balloon angioplasty have been reported including arterial rupture, delayed perforation and fracture of microsurgical blades. Here we report a very unusual and inadvertent extraction of a stent previously deployed in the ramus intermedius coronary branch by a cutting balloon catheter. This required repeat stenting of the same site for an underlying dissection. Even though stent extraction is a rare complication it can be serious due to dissection, perforation, and closure of the artery. Physicians performing coronary artery interventions would need to be aware of this rare and serious complication especially if any difficulty is encountered while withdrawing the cutting balloon. Therefore, after removal, cutting balloon should be examined thoroughly for possible stent dislodgment or extraction when used for “in-stent restenosis.”